Use of implicit performative utterances at University of Padjadjaran and at University of Pennsylvania - Rosaria Mita Amalia (Universitas Syiah Kuala, 2017)
The use of implicit performative utterances can be found in some announcements at Universitas Padjadjaran (Unpad) in Bandung, Indonesia and at the University of Pennsylvania (UPenn) in Philadelphia, U. S. A. In linguistics, there is a form of speech known as performative utterances (Austin, 1962). The word comes from the verb ‘perform’ and refers to the noun ‘action’; it is said that the word refers to a speech for performance or action. Performatives cannot be regarded as right or wrong statements, but refer to appropriate or inappropriate, legitimate or illegitimate actions. Implicit performatives are performative utterances with performative verbs but they are not explicitly stated. With an implicit performative, the sentence does not have an explicit performative verb, but it has illocutionary force which is known from the context. Knowing the context, the hearer assumes the performative verb that appears. The use of this kind of utterances in notices at Unpad and at UPenn is quite different. This paper examines the differences and the similarities between the announcements at Unpad and at UPenn which use implicit performative utterances.